Combined Plyometric Trainings and its Effectiveness in Improving Muscle Strength and Power among Male Adolescents - Shidqi Hamdi Pratama Putera; Achmad Widodo; Heri Wahyudi; Himawan Wismanadi; Abdul Rachman Syam Tuasikal; Anindya Maratus Sholikhah (Physical Education Theory and Methodology, 2025)
Objectives.  This study aimed to evaluate the impact of combined plyometric training on increasing muscle strength and explosive power among male high school students.